Re-evaluation of stratigraphic sections of the Tilatá formation, Sabana de Bogotá, eastern Cordillera of the Colombian Andes (2016)
Three new localities on the Pliocene of the Sabana de Bogotá are described in order to show their potential to be subjected tofuture paleoclimate and paleoelevation studies,which will helpdistinguish wherever previous studiesrecorded climate changes or uplifton the late Neogene. The Sotaquira section of the Tilatá Fm. was deposited in a floodplain,and haveadatable bed and organic rich sediments appropriate to undertake further studies(i.e. biomarkers)..The Rio Frio localities of the Chorrera Fm. constitute the deposits of alluvial fans in which one probably datable horizon was recovered. While the Mondoñedo sections of the Balsillas Fm. lack of organic and ash bearing deposits,butinterestingpaleosols and macrofossils of Humiriaceae and Asteraceae were found...